Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/adfm.201909014
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Zirconium Phosphate under Nanoconfinement with Superior Adsorption Capability for Water Treatment

Abstract: In confined space with length scale of several nanometers, the phase behavior of matter, e.g., nucleation and crystallization, is completely different from its analogue in bulk. However, in environmental applications, the relationship between the nanoconfined crystallization behavior of inorganic crystals and their properties for pollutant removal is rarely elucidated. Herein, an unusual formation of zirconium phosphate (ZrP) crystals as a mixture of both thermodynamically stable α‐ and metastable γ‐phases ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…A mesoporous polystyrene (MPS) matrix was also used to immobilize ZrP [ 60 ]. According to this procedure, the MPS host was first prepared by a flash freezing method, which allowed the acquisition of spherical beads of 1.5–2.0 mm in diameter, with abundant uniform pores of around 7.9 nm.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…A mesoporous polystyrene (MPS) matrix was also used to immobilize ZrP [ 60 ]. According to this procedure, the MPS host was first prepared by a flash freezing method, which allowed the acquisition of spherical beads of 1.5–2.0 mm in diameter, with abundant uniform pores of around 7.9 nm.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…246,266−268 Zhang et al in 2020 reported the synthesis of mixed-phase, thermodynamically stable α-ZrP and metastable γ-ZrP encapsulated within 7.9 nm mesopores created by mesoporous polystyrene (MPS). 246 The nanoconfinement offered by MPS alters the interaction between ZrP and Pb(II) ions from nonspecific electrostatic attraction to specific inner-sphere coordination as shown in Figure 21c. The nanocomposite, ZrP@ MPS surprisingly shows high adsorption capacity and selectivity with K d values 10−90 times higher than for nonconfined α-ZrP.…”
Section: Ion Exchange and Sorption Of Metal Ionsmentioning
confidence: 99%
“…(C) Schematic illustration of lead ion adsorption by the ZrP formed inside (a) confined space and (b) the α-ZrP. Reproduced with permission from ref . Copyright 2020 Wiley-VCH.…”
Section: Ion Exchange and Sorption Of Metal Ionsmentioning
confidence: 99%
“…Moreover, surface functionality enhances the hydrophilicity of the polymer composite and hence improves the heavy metal removal. For instance, a published study found that the adsorption of mesoporous polystyrene for metal ions can be enhanced using zirconium phosphate (ZrP) in nanoconfinement (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%